The Environmental Dimensions of Islam: By Mawil Izzi Dien (Cambridge: The Luttenvorth Press, 2000. 190 pages.) (American Journal of Islam and Society, 2002)
Dr. Mawil Izzi Dien, Senior Lecturer in Islamic Studies at the University ofWales, has been writing about Islam and environmental issues for almosttwo decades. The Environmental Dimensions of Islam is a summary of hisprevious writings presented together with new additions. Izzi Dien is oneof the most prominent scholars in the new discourse of Islamic ecotheology,although he himself seldom refers to other Muslim scholars in this field,which somehow gives the wrong impression that he is the only one amongMuslims dealing with environmental issues.After a short introductory chapter, Izzi Dien discusses in chapter 2"The Environment and Its Components in Islam." This chapter gives aninformative introduction to Qur'anic terminology on various environmentalcomponents and their status in Islam, such as water, earth, living organisms,diversity and biogeological cycles.This Qur'anic terminology is further developed in chapter 3, deaLingwith theology pertaining to the environment. This chapter deals with issuessuch as the question of creation and the unseen and the Divine origin ofeverything: constancy, comprehensiveness, balance, and universal laws innature as the Creation. I sympathize with much of the argument presentedregarding the role of human beings in Creation, i.e., their trusteeship, partnershipand responsibility. This chapter would have been strengthened by adiscussion of the accusations from the environmental movement that themonotheistic religions represent an anthropocentric, and thus problematic,view of nature. For instance, the idea expressed in the Qur'an that God madenature subservient ????·akhkhara) to human beings may be criticized (seeQur'anic verses 2:29; 45:12-13; and 14:33-34), but the author chooses notto discuss this concept at all or to refer to other scholars' criticisms.Another problem is his unusual definition of positivism, a philosophyheld accountable for promoting a hegemonic position of science associatedwith a problematic view of nature. He sees positivism as something thatIslam promotes, as in his view, it implies that human beings "are an active,positive force placed on this earth to construct, improve, and reform it." lnthe Qur'an we read about examples of how people who destroyed their ownhabitat were punished by God in the form of ecocatastrophes ...